Comparison of Actual and Reference Evapotranspiration Between Seasonally Frozen and Permafrost Soils on the Tibetan Plateau - Lianglei Gu; Jimin Yao; Zeyong Hu; Yaoming Ma; Haipeng Yu; Fanglin Sun; Shujin Wang (Remote Sensing, 2025)
A comparison of evapotranspiration between seasonally frozen and permafrost soils has important theoretical value for studying land surface processes and ecological environmental evolution on the Tibetan Plateau. In this work, the actual ( ET a ) and reference ( ET 0 ) evapotranspiration and crop coefficient ( K c ) were calculated via eddy covariance data and meteorological gradient data from sites in the Naqu Prefecture and Tanggula Mountains. The variations, differences, and factors influencing the ET a and ET 0 were analysed. The results revealed that at the two sites in 2008, the annual total ET a values were 493.53 and 585.17 mm, which accounted for 83.58% and 144.39% of the total annual rainfall, respectively. The ET a at the Naqu site was affected mainly by the Tibetan Plateau monsoon (TPM), whereas the ET a at the Tanggula site was strongly affected by both the TPM and the freezing–thawing processes of the permafrost. The annual total ET 0 values at the two sites were 819.95 and 673.15 mm, respectively. The monthly total ET 0 at the Naqu site was greater than that at the Tanggula site. The ET a and ET 0 values at the two sites were low in winter–spring, high in summer–autumn, and concentrated from May to October. When snow was present, the ET a values at the Naqu site were relatively high, and the ET 0 values at both sites were very small and even negative at the Naqu site. The ET a and ET 0 values at the two sites were significantly positively correlated with the net radiation ( R n ), surface temperature ( T 0 ), air temperature ( T a ), water vapour pressure ( e ) and soil water content ( smc ), and negatively correlated with the wind speed ( ws ). The correlation between the ET a and the T 0 at the Naqu site was the most significant, and the coefficient of partial correlation was 0.812; meanwhile, the correlation between the ET a and the smc at the Tanggula site was the most significant, and the coefficient of partial correlation was 0.791. The R n at the Naqu and Tanggula sites both had greater ...